Analysis of the Government's Role in Empowering Fishermen Communities in Majene District - Marlina Rajab; Juanda Nawawi; A M Rusli (Jurnal Office, 2022)
Poverty is a problem that is currently still a problem in the lives of fishing communities . This article aims to analyze the role of the government in empowering fishing communities in Majene Regency as well as the obstacles of the local government in empowering fishing communities. This writing uses the descriptive method. Data collection techniques using interviews, observation, and documentation then the data obtained will be analyzed using qualitative techniques. The results showed that the role of the local government in empowering fishing communities was not optimal, while several empowerment programs carried out by the local government included training and fostering fisherman and fishermen's wives, mentoring field extension workers, and assistance with facilities and infrastructure. Meanwhile, the obstacles that become obstacles to the local government include budgets and binding regulations,